Српски - Аврамовић, Драгутин; Jovanov, Ilija D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In a modern society that pretends to be "democratic", political oratory plays an essential role. Politicians generally use their speeches to inform citizens about topics that are important to their daily lives or to motivate them to take certain actions. In order to be successful in this, they must master the general rules of rhetoric and the special skills that relate exclusively to this type of oratory. This paper analyzes the speeches of James David Vance and Ursula von der Leyen, which were delivered at the Munich Security Conference in 2024 and 2025, in order to determine similarities and differences in certain styles of oratory. Having in mind that the importance of oratory in the USA is generally greater than in Europe, as well as the tradition that orators on the other side of the Atlantic are educated not only in accordance with the classical rules of rhetoric but also according to the norms of public speaking, the initial assumption about different styles turned out to be quite correct in the final analysis.